2008
DOI: 10.1142/s0217984908016054
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Silicon-Molecular Electronics

Abstract: As CMOS technology extends beyond the current technology node, many challenges to conventional MOSFET were raised. Non-classical CMOS to extend and fundamentally new technologies to replace current CMOS technology are under intensive investigation to meet these challenges. The approach of hybrid silicon/molecular electronics is to provide a smooth transition technology by integrating molecular intrinsic scalability and diverse properties with the vast infrastructure of traditional MOS technology. Here we discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Three diruthenium alkynyl compounds with organophosphonate capping groups have been prepared, and these compounds retain the key features of the electronic structure of the unsubstituted precursors, especially the rich redox activity and small energy gaps. Compounds 2 and 3 are attractive candidates for device fabrication because of their bicapping nature . Compound 3 can be sandwiched between two layers of dielectric oxide upon the cleavage of tert -butyls using Me 3 SiCl/Et 3 N, while compound 2 can be incorporated into a metal–molecule–insulator junction upon stepwise removal of tert -butyl and TMSE groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three diruthenium alkynyl compounds with organophosphonate capping groups have been prepared, and these compounds retain the key features of the electronic structure of the unsubstituted precursors, especially the rich redox activity and small energy gaps. Compounds 2 and 3 are attractive candidates for device fabrication because of their bicapping nature . Compound 3 can be sandwiched between two layers of dielectric oxide upon the cleavage of tert -butyls using Me 3 SiCl/Et 3 N, while compound 2 can be incorporated into a metal–molecule–insulator junction upon stepwise removal of tert -butyl and TMSE groups.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds 2 and 3 are attractive candidates for device fabrication because of their bicapping nature. 7 Compound 3 can be sandwiched between two layers of dielectric oxide upon the cleavage of tert-butyls using Me 3 SiCl/ Et 3 N, 8 while compound 2 can be incorporated into a metal− molecule−insulator junction upon stepwise removal of tertbutyl and TMSE groups. These aspects are being pursued in our laboratory through collaboration with device engineers.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…It has been suggested that redox-active molecules supported on the native oxide (SiO 2 ) surface of a Si wafer may be key to the realization of hybrid electrolyte− molecule−silicon capacitors. 20 We reported previously the synthesis of Ru 2 (ap) 4 -CC-4-C 6 H 4 -P(O)(O t Bu) 2 with a ditert-butylphosphonate-arylacetylide ligand attached at the "0" site (definitions of "0" and "4" sites are given in Chart 1) and its derivative trans-( 4 (5), where the di-tert-butylphosphonate-arylacetylide is attached at the "4" site.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that the HOMO and LUMO energy levels of the molecule on-device agreed well with the values obtained from the voltammetric measurement in bulk solution, demonstrating the molecular origin of the observed conductance switching. It has been suggested that redox-active molecules supported on the native oxide (SiO 2 ) surface of a Si wafer may be key to the realization of hybrid electrolyte–molecule–silicon capacitors . We reported previously the synthesis of Ru 2 ( ap ) 4 -CC-4-C 6 H 4 -P(O)(O t Bu) 2 with a di- tert -butylphosphonate-arylacetylide ligand attached at the “0” site (definitions of “0” and “4” sites are given in Chart ) and its derivative trans- (4-Me 3 SiC 2 H 4 S-4-C 6 H 4 -CC)-Ru 2 ( ap ) 4 -CC-4-C 6 H 4 -P(O)(O t Bu) 2 , which contain a protected phosphonate group that can form strong covalent bonds with SiO 2 upon deprotection.…”
Section: Introductionmentioning
confidence: 99%